2018
DOI: 10.1098/rspb.2018.2084
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the roles of CMK-1 and OGT-1 in interstimulus interval-dependent habituation inCaenorhabditis elegans

Abstract: Habituation is a ubiquitous form of non-associative learning observed as a decrement in responding to repeated stimulation that cannot be explained by sensory adaptation or motor fatigue. One of the defining characteristics of habituation is its sensitivity to the rate at which training stimuli are presented—animals habituate faster in response to more rapid stimulation. The molecular mechanisms underlying this interstimulus interval (ISI)-dependent characteristic of habituation remain unknown. In this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 54 publications
5
40
0
Order By: Relevance
“…Surprisingly, epistasis analysis (see Box ) revealed that they act in parallel for habituation of response distance—the habituation impairment of double mutants was more pronounced than either single mutant . These results were demystified when we broke response distance into its two core components, response duration and response speed, and found that cmk‐1 primarily affected habituation of response speed, while ogt‐1 primarily affected response duration . These results and those described previously raise a difficult epistemological question: how many behavioral components of habituation should be measured to accurately investigate all of its underlying mechanisms?…”
Section: Further Recent Evidence That Habituation Of Different Responmentioning
confidence: 63%
See 3 more Smart Citations
“…Surprisingly, epistasis analysis (see Box ) revealed that they act in parallel for habituation of response distance—the habituation impairment of double mutants was more pronounced than either single mutant . These results were demystified when we broke response distance into its two core components, response duration and response speed, and found that cmk‐1 primarily affected habituation of response speed, while ogt‐1 primarily affected response duration . These results and those described previously raise a difficult epistemological question: how many behavioral components of habituation should be measured to accurately investigate all of its underlying mechanisms?…”
Section: Further Recent Evidence That Habituation Of Different Responmentioning
confidence: 63%
“…The observation that both cmk‐1 and ogt‐1 function in the same cells of the tap‐withdrawal circuit to influence habituation of response distance in remarkably similar ways prompted us to test whether they functioned as part of a single ISI‐sensitive pathway underlying habituation. Surprisingly, epistasis analysis (see Box ) revealed that they act in parallel for habituation of response distance—the habituation impairment of double mutants was more pronounced than either single mutant . These results were demystified when we broke response distance into its two core components, response duration and response speed, and found that cmk‐1 primarily affected habituation of response speed, while ogt‐1 primarily affected response duration .…”
Section: Further Recent Evidence That Habituation Of Different Responmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on sensory habituation in C. elegans and Aplysia, and startle habituation in zebrafish and rodents have revealed that the synapses between sensory afferents and 'command' interneurons undergo plasticity during habituation [12][13][14][15][16][17] . Furthermore, genetic screens in C. elegans and Drosophila have been instrumental in identifying genes that regulate habituation learning [18][19][20][21][22][23][24][25][26][27][28] . Thus, while a picture of habituation in invertebrates is emerging, a comprehensive view of vertebrate habituation learning is largely absent.…”
Section: Introductionmentioning
confidence: 99%